Representações da identidade nacional na campanha publicitária Keep walking, Brazil - Fraga, Pauline Neutzling and Silveira, Ada Cristina Machado (Cadernos de Comunicação, 2017)
O artigo ocupa-se da investigação das representações de brasilidade presentes na campanha publicitária Keep walking, Brazil (2011), da marca Johnnie Walker. Como objetivo geral pretendeu-se investigar quais os principais traços da identidade nacional brasileira presentes na campanha e as prováveis relações de poder implícitas, considerando-se as formas simbólicas propostas.Palavras chave: Mídia; Representações; Identidade cultural; Narrativa publicitária; Brasilidade.Las representaciones de la identidad nacional en la campaña de publicidad Keep walking, BrazilResumen: El artículo trata de la investigación de las representaciones presentes en la campaña publicitaria Keep Walking, Brazil (2011), de la marca Johnnie Walker. Como objetivo general se pretende investigar cuáles son las principales características de la identidad nacional brasileña presentes en la campaña y las probables relaciones del poder implícitas, considerando las formas simbólicas propuestas.Palabras clave: Medios de comunicación; Representaciones; Identidad cultural; Narración publicitaria. Brasilidad.Representations of national identity in the advertising campaign Keep walking, BrazilAbstract: The article deals with the investigation of the Brazilianness present representations in the hype Keep walking, Brazil (2011), by brand Johnnie Walker. As a general objective was intended to investigate what the main features of Brazilian national identity in the present campaign and the probable relationship of implied power, considering that the symbolic forms proposed.Key words: Media; Representations; Cultural Identity; Narrative Advertising; Brasility.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTkwMi8yMzE2ODgyeDI1NzU2